2015
DOI: 10.4103/0019-5545.171837
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yoga therapy for the management of psychopathology of patients having chronic schizophrenia

Abstract: Background:There is a large body of literature and scientific data regarding the efficacy of pharmacological and psychosocial interventions for schizophrenia, however, studies on Yoga therapy is scanty. Yoga is a means of balancing and harmonizing the body, mind and emotion, and for enlightening the mind and upliftment of the total personality.Aims:The present study was conducted to determine the efficacy of Yoga therapy as an adjunctive therapy and to see its effects on psychopathology on the patients sufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…To be precise, after 4 months of practicing yoga, patients showed a significant reduction in the presence of psychopathological symptoms, as well as an improvement in prosocial activity and quality of life. Similar results have also been found in other studies devoted to the above problem (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). The results of a study conducted with 95 respondents (Deuskar, 2010) showed that practicing yoga nidra 8 for a month and a half significantly reduced the symptoms of stress, which was confirmed by other similar studies (Malathi & Damodaran, 1999;Potey et al, 2016).…”
Section: Yoga the Results Of Scientific Research And Mental Healthsupporting
confidence: 84%
See 1 more Smart Citation
“…To be precise, after 4 months of practicing yoga, patients showed a significant reduction in the presence of psychopathological symptoms, as well as an improvement in prosocial activity and quality of life. Similar results have also been found in other studies devoted to the above problem (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). The results of a study conducted with 95 respondents (Deuskar, 2010) showed that practicing yoga nidra 8 for a month and a half significantly reduced the symptoms of stress, which was confirmed by other similar studies (Malathi & Damodaran, 1999;Potey et al, 2016).…”
Section: Yoga the Results Of Scientific Research And Mental Healthsupporting
confidence: 84%
“…У конкретном случају, након 4 мјесеца практиковања јоге пацијенти су показали значајно смањење присутних психопатолошких симптома као и побољшање просоцијалног дјеловања и квалитета живота. До сличних резултата, дошла су и друга истраживања посвећена наведеној проблематици (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). Резултати истраживања спроведеног са 95 испитаница (Deuskar, 2010) указују да је практиковање јога нидре 8 у периоду од мјесец и по дана, значајно довело до смањења симптома стреса, што потврђују и друга слична истраживања (Malathi & Damodaran, 1999;Potey et al, 2016).…”
unclassified
“…[1314151617181920] The mean age ranged from 21.50 ± 3.21[21] to 65.5 ± 4.8[20] years in the YT studies and from 23.8 ± 6.8[13] to 53.2 ± 6.1[12] years in the MBI studies. YT and MBI studies included both genders, but few YT studies included either men[1822] or women,[1723] and one MBI study included only men. [6] Number of women in MBI studies ranged from 1[12] to 66.…”
Section: Resultsmentioning
confidence: 99%
“…[13] The patient group comprised mostly individuals with a diagnosis of either schizophrenia, MDD, or BD as per the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, except for a few studies which used the ICD-10 criteria. [18222425] Apart from individuals with schizophrenia, a few studies included certain other disorders such as schizoaffective disorder,[612172627] unspecified psychosis,[7172128] schizophreniform, brief psychotic and delusional disorders,[17] and psychotic depression. [1429] In YT studies, baseline mean total positive and negative syndrome scale (PANSS) score varied from 47.5 ± 15.4[17] to 85.10 ± 19.82[10] and positive subscale score ranged from 10.2 ± 3.7[17] to 21.60 ± 5.99.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation